2017
DOI: 10.1080/15592324.2017.1295907
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant one-zinc-finger protein 2 is localized both to the nucleus and stress granules under heat stress in Arabidopsis

Abstract: VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 have an ability to bind to the specific cis-element in the AVP1 promoter of Arabidopsis, which function on the PhyB-dependent flowering and possibly in various stress responses as potential transcription factors, although nuclear localization of VOZ proteins is still unclear. In this study, we found that VOZ2 is dispersed throughout the cytoplasm under normal growth conditions, whereas VOZ2 is transferred not only to the nucleus but also to the cytoplasmic foci un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
3
34
0
1
Order By: Relevance
“…Colocalization studies with the stress granule marker, G3BP-RFP in N. benthamiana transiently expressing ArathEULS3 suggested that the lectin is relocated to stress granules after the plant has been subjected to certain stresses. Similar results were reported for other plant proteins such as the polyadenylated (poly(A)+) mRNA binding protein PAB-2 [7] and the VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 [36], which in normal conditions localize to the cytoplasm and the nucleus, and are translocated to stress granules upon stress. However, despite the fact that ArathEULS3 transcript levels are known to be upregulated in response to drought stress the ArathEULS3 protein was not identified in the proteome of heat/dark treated plants [10] nor was it identified when examining the changes in RNA-binding proteome under drought stress conditions [9,37].…”
Section: Discussionsupporting
confidence: 83%
“…Colocalization studies with the stress granule marker, G3BP-RFP in N. benthamiana transiently expressing ArathEULS3 suggested that the lectin is relocated to stress granules after the plant has been subjected to certain stresses. Similar results were reported for other plant proteins such as the polyadenylated (poly(A)+) mRNA binding protein PAB-2 [7] and the VASCULAR PLANT ONE-ZINC FINGER (VOZ)1/and VOZ2 [36], which in normal conditions localize to the cytoplasm and the nucleus, and are translocated to stress granules upon stress. However, despite the fact that ArathEULS3 transcript levels are known to be upregulated in response to drought stress the ArathEULS3 protein was not identified in the proteome of heat/dark treated plants [10] nor was it identified when examining the changes in RNA-binding proteome under drought stress conditions [9,37].…”
Section: Discussionsupporting
confidence: 83%
“…These include the purported calcium sensor CALMODULIN-LIKE38 (CML38), which reversibly accumulates into SGs under hypoxic conditions in a Ca 2+ -dependent manner (Lokdarshi et al, 2016), and the NAM (no apical meristem), ATAF (Arabidopsis transcription activation factor), and CUC (cup-shaped cotyledon) family transcription factor VASCULAR PLANT ONE-ZINC-FINGER2 (VOZ2), which translocates from the cytosol to the nucleus and SGs/PBs during heat stress (Koguchi et al, 2017). AtCML38 function contributes to hypoxia tolerance (Lokdarshi et al, 2016), but it remains to be discovered how AtVOZ2 incorporation into SGs/PBs under heat stress contributes to mRNA metabolism and if this influences heat stress tolerance.…”
Section: Mrna Sequestration In Sgs: a Transit Depot Between Translatimentioning
confidence: 99%
“…In Arabidopsis, voz1voz2 double mutants exhibited enhanced tolerance to freezing and drought stress but increased resistance to C. higginsianum and a bacterial pathogen, Pseudomonas syringae [21,22]. Recently, it was found that VOZ1 and VOZ2 mediated high-temperature stress response by independently suppressing the expression of DREB2C or DREB2A in Arabidopsis [23,24]. In contrast to freezing and drought stress, VOZ transcription factors play opposite roles in response to salt stress.…”
Section: Introductionmentioning
confidence: 99%